The Level of Ability of Basic Backhand Short Serve Techniques in Badminton Learning - Junanda, Hendya Alif; Hidayatullah, Hafiz (Journal of Physical and Outdoor Education, 2024)
The purpose of this study was to determine the ability of students to perform a short backhand serve in badminton learning. This study uses a quantitative descriptive method using measurements and tests used in data collection. The population of this study were all third-level students at STKIP Pasundan with a total of 300 and sampling using cluster random sampling with a total of 45 people. The results of the study were 12 people in the excellent category with a total percentage of 27%, while 31 people got the good category with a percentage of 69% and 2 people got the less category with a total percentage of 4%..